Kritik Atas Pandangan Inovasi-Kewirausahaan J. A. Schumpeter - Rijal Assidiq Mulyana (Universitas Negeri Surabaya, 2023)
Schumpeter is one of the 20th century economists who laid brilliant ideas about entrepreneurship. He placed innovation as the soul of entrepreneurship. An individual is considered an entrepreneur when they have made innovation through new combinations that include several things, such as new products, new production methods, new markets, new sources of supply, and more effective organizational management. This study aims to conduct a critical review and commentary on Schumpeter's ideas. In practice, Schumpeter's ideas about innovation have limitations. The author sees these limitations in several aspects: 1. The innovation Schumpeter referred to may only occur in established industries or those with strong economic capital, meaning that innovation only occurs among large-scale business players, but in practice, entrepreneurs do not necessarily have large-scale business operations from the beginning. 2. Schumpeter emphasizes the functions of innovation too much but overlooks the potential risks that business players may face when carrying out innovative functions. 3. Business players who manage their business, business products, production methods with traditional and outdated mindsets and methods may emerge, and these types of business players cannot be recognized based on Schumpeter's theory.